Qualitative and quantitative evaluation of small and medium-sized rivers based on data resources. Issue 3 (May 2019) - Fu, Lei; Wang, Junmin; You, Aiju; Yu, Jia; Yang, Yi
Abstract: Over the past three centuries, due to the improvement of the understanding of the natural environment and social service function of rivers, many countries in the world have started the research and practice of river health evaluation. However, the connotation and definition of river health has not formed a unified standard around the world. Recently, there are many studies on the ecological health of large rivers in China, and a relatively acceptable hydrological and water quality monitoring system has been established for those large rivers. However, the health evaluation of various small and medium-sized rivers is still in the preliminary stage. Though many commonly used evaluation methods have been introduced in China, it is still difficult to carry out health evaluation in small and medium-sized River areas due to the lack of basic data, the difficulty of real-time monitoring, the complexity of index calculation formula and other factors. Based on the current situation of construction, management and monitoring of small and medium-sized rivers in China, this study uses qualitative and quantitative methods to evaluate the health of typical small and medium-sized rivers, and compares the evaluation systems and results of the two methods in order to find a suitable river health evaluation method for typical small and medium-sized rivers in China under limited data resources.